Humanization of education as a prerequisite for forming the students‟ tolerance in higher educational institutions - Nadiia Yashyn (Vasyl Stefanyk Precarpathian National University, 2017)
The article deals with the problem of forming the students' tolerance in the context ofhumanization of modern higher education. The analysis of the scientific and pedagogicalliterature on the problem is conducted. The meanings of the concepts "humanization" and"humanism" are determined. The peculiarities of humanization of higher education areexamined. The role of tolerance in the system of humanistic values is shown. Key words: humanization, tolerance, humanism, higher education, humanity, humanisticoutlook, personality, upbringing.